2021
DOI: 10.1002/pmrj.12537
|View full text |Cite
|
Sign up to set email alerts
|

Physical Medicine and Rehabilitation Faculty Diversity Trends by Sex, Race, and Ethnicity, 2007 to 2018 in the United States

Abstract: Introduction Sex and race/ethnicity disparities persist in academic Physical Medicine and Rehabilitation (PM&R). This study contributes to the current body of knowledge by demonstrating changes in academic PM&R by sex and race/ethnicity in multiple categories over a 12‐year period. Objective To evaluate workforce disparities in academic PM&R by measuring sex and race/ethnicity diversity in academic degree, rank, and tenure status. Design Surveillance study. Setting and Methods Self‐reported data for PM&R from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 33 publications
(79 reference statements)
0
28
0
Order By: Relevance
“…9 Interestingly, a study done looking at the trend of female chairs from 2007 to 2018 found the number of female chairs in PM&R fell by 10% over this period. 4 The majority of the female chairs reported experiencing gender discrimination in the workplace, whereas more men experienced discrimination in the workplace due to ethnicity/race. This is likely due to only 14% of the chairs (2 of 15) being non-White women versus 29.4% of the chairs (10 of 34) being non-White men, therefore more likely to experience discrimination due to ethnicity/race.…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Interestingly, a study done looking at the trend of female chairs from 2007 to 2018 found the number of female chairs in PM&R fell by 10% over this period. 4 The majority of the female chairs reported experiencing gender discrimination in the workplace, whereas more men experienced discrimination in the workplace due to ethnicity/race. This is likely due to only 14% of the chairs (2 of 15) being non-White women versus 29.4% of the chairs (10 of 34) being non-White men, therefore more likely to experience discrimination due to ethnicity/race.…”
Section: Demographicsmentioning
confidence: 99%
“…Although many aspire to become chair, very few are able to achieve this prestigious role. Historically, in academic medicine and more specifically in physical medicine and rehabilitation (PM&R), women and ethnic/racial minorities have always been underrepresented with the most significant disparity noted at the chair level 2–4 …”
mentioning
confidence: 99%
“…The pandemic has had and will continue to have a profound effect on the health care workforce, and the negative impact it has on women physicians and scientists may last throughout their careers. The pandemic has exacerbated preexisting disparities for many women in medicine, including physiatrists 38‐40 . For example, there were already pay and promotion inequities and during the pandemic many women took pay cuts or had a decrease in clinical revenue owing to budget cuts at work or increased childcare or eldercare responsibilities at home 41…”
Section: A Special Consideration For the Widening In The Workforce Di...mentioning
confidence: 99%
“…These visual representations of the medical culture reinforce the acceptable norms and values, White and masculine, in medicine. This disproportionate representation is discernible across multiple subspecialties of medicine, National Institutes of Health funding, professional societies, medical journals' editorial boards, and clinical trials [7][8][9][10][11][12]. Similar gender and racial disparity persist in the specialty of Internal Medicine [13].…”
Section: Introductionmentioning
confidence: 99%